Efficacy and Safety of Roflumilast in Asthma Management: A Systematic Review and Meta-Analysis - Alruwaili, Musaad; Alamer, Rakan Fahad; Ahmed, Raneem; Alanzi, Hajar; Alsabhan, Rahaf; Alhamzani, Faisal; Alrashidi, Hanadi; Alanzi, Ryam; Alshammari, Emtenan; Alshammari, Nada; Alrashidi, Mnsorha; Al-Humian, Hmoud; et al. (ENT Updates, 2025)
Asthma is a chronic respiratory condition affecting millions globally, causing significant morbidity and economic burden. Despite advances in treatment, many patients experience uncontrolled symptoms and exacerbations, particularly those with corticosteroid resistance or neutrophilic inflammation. Roflumilast, an oral phosphodiesterase-4 inhibitor, may offer additional benefits by targeting inflammatory pathways that are not fully controlled by standard therapy. This systematic review and meta-analysis aimed to assess the efficacy and safety of roflumilast in patients with asthma. A comprehensive literature search was conducted using the PubMed, Scopus, and Web of Science databases from January 2015 to August 2025. We included randomized controlled trials and pooled analyses evaluating roflumilast in patients with asthma. The primary outcome was the mean difference in the forced expiratory volume in one second between the intervention and control groups. Secondary outcomes included risk of exacerbation, symptom control, and adverse events. Six studies met the inclusion criteria, with 2845 participants. Roflumilast showed a modest improvement in forced expiratory volume in one second (Mean difference: +0.04 L; 95% confidence interval: −0.01 to +0.09; heterogeneity = 41%), which was not statistically significant. Exacerbation risk reduction was inconsistent across studies (Risk ratio: 0.96; 95% confidence interval: 0.83–1.12; heterogeneity = 35%). Adverse events, particularly gastrointestinal issues and weight loss, were more frequent with roflumilast, leading to higher rates of discontinuation. Subgroup analysis suggested potential benefits in patients with persistent airway inflammation or corticosteroid resistance, whereas harm was observed in obese patients. The limited number of trials and heterogeneity among studies restricted the conclusiveness of our findings.